Elemental Two‐Dimensional Materials for Li/Na‐Ion Battery Anode Applications - Tian, Yahui; Chen, Ya; Liu, Yaoda; Li, Hui; Dai, Zhengfei (Chemical record, 2022)
Two‐dimensional (2D) nanostructure is currently the subject in the fields of new energy storage and devices. During the past years, a broad range of 2D materials represented by graphene have been developed and endow with excellent electrochemical properties. Among them, elemental 2D materials (Xenes) are an emerged material family for Li/Na‐ion battery (LIB/SIB) anodes. Compared with other 2D materials and bulk materials, Xenes may exhibit some great superiorities for Li/Na storage, including excellent conductivity, fast ion diffusion and large active sites exposure. In this review, we provide a systematic summary of the recent progress and achievements of Xenes as well as their applications in LIBs/SIBs. The broad categorization of Xenes from group IIIA to VIA has been concisely outlined, and the related details in syntheses, structures and Li/Na‐ion storage properties are reviewed. Further, the latest research progress of Xenes in Li/Na ion batteries are summarized, together with mechanism discussions. Finally, the challenges and prospects of Xenes applied to Li/Na ion battery are proposed based on its current developments. In this review, elemental 2D materials and their applications in Li/Na storage have been concisely outlined and systematically summarized from group IIIA to VIA. Preparation methods and structures are described and compared. Latest research progress of elemental 2D materials in Li/Na ion batteries are summarized and discussed with future challenges and prospects for elemental 2D materials in Li/Na‐ion batteries.